Invention and Global Diffusion of Technologies for Climate Change Adaptation : A Patent Analysis - Dechezlepretre, Antoine; Fankhauser, Sam; Glachant, Matthieu; Stoever, Jan; Touboul, Simon (World Bank, Washington, DC, 2020)
The Earth's climate has already begun to change and will inevitably continue to do so. Even if the targets set in the Paris Agreement are met—to keep the global surface temperature increase below 2 degrees Celsius relative to preindustrial levels—many regions will still suffer severely from the consequences of climate change. They will have more frequent extreme weather events, changes in precipitation patterns, rising sea levels, temperature increases, and many other related effects (IPCC 2018). In this context, technology is certainly a major tool to increase societies’ ability to adapt to the adverse effects of climate change (Klein and Tol 1997; Miao 2017; GCA 2019). International technology transfer hence becomes particularly important because a large fraction of the innovation activity in today's knowledge-based economy takes place in the Global North, while technologies for climate change adaptation are urgently needed in low- and middle-income countries, which are particularly vulnerable to climate shocks (Fankhauser and McDermott 2014) Increasing the availability of technology in vulnerable countries requires knowledge of the current geography of innovation. To that end, this report uses patent data to describe and quantify the invention and global diffusion of technologies for climate change adaptation over recent decades based on a global patent database. Importantly, relying on patent data restricts the scope of the analysis to solutions for adaptation that are at the technological frontier and excludes the role of nontechnological forms of innovation and low-tech options. A particular emphasis is put on the case of low- and middle-income countries, which combine high vulnerability to climate change with low technological resources. The analysis relies on patent data from the World Patent Statistical Database (PATSTAT), maintained by the European Patent Office (EPO), which covers the population of patents filed worldwide. We use the EPO's new "Y02A" category to identify all patents in PATSTAT pertaining to "technologies for adaptation to climate change." The classification was released in April 2018 and has so far never been used in empirical analyses. Although innovation scholars and analysts widely use patent data to map technology fields, such data do have some drawbacks, as the report discusses. The patent data are thus complemented with data on foreign direct investment (FDI), which allow us to test the robustness of the results on technology transfer.